Recitation as an Instrument of Tafsir: Thematic Study of QS. Al-Baqarah Verses 196 and 222 From the Perspective of Classical and Contemporary Scholars - Muhammad Jihad Azni Lubis; M Kaisar Rohman; Achyar Zein; Rahayu Fuji Astuti (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to explore the role of qira’at as an instrument of thematic interpretation, especially in QS. Al-Baqarah verses 196 and 222, and its implications for the istinbath of fiqh law. Using an interpretive qualitative approach with a literature study method, this study examines primary sources such as Jāmi‘ al-Bayān (al-Ṭabarī), Al-Jāmi‘ li Aḥkām al-Qur’ān (al-Qurṭubī), Mafātīḥ al-Ghayb (al-Rāzī), and qira’at literature such as An-Nashr fī al-Qirā’āt al-‘Ashr (Ibn al-Jazārī) and Manāhil al-‘Irfān (al-Zarqānī). The results of the study show that the difference in readings in the wording of al-'umrah (nashab vs rafa') affects the legal status of umrah (obligatory or sunnah), while the readings of yathurna vs yattaharna have an impact on the conditions for the permissibility of postmenstrual husband-wife relations. The integration of qira'at into thematic interpretation shows its potential in bridging differences in schools of thought, enriching legal analysis, and responding to the challenges of contemporary fiqh inclusively. This study confirms that qira'at mutawatir is not only a linguistic source, but also a legitimate epistemic foundation in the development of Islamic interpretation and law.